The Role of the United States Supreme Court in Shaping Federal Drug Policy - Griffin, O. Hayden (American journal of criminal justice, 2014)
Through judicial review, the United States Supreme Court has played a pivotal role in deciding and/or interpreting the constitutionality of legislation. Since the passage of the Pure, Food and Drug Act in 1906, the Supreme Court’s role has been integral in formulating drug policy. In some instances, the Court’s decisions have limited the authority of the federal government, while in others have greatly expanded this authority. As a direct result of the decision-making of the Supreme Court, limitations have periodically been placed on Congress to regulate controlled substances. Many people, who were perceived as medical patients, became criminal drug users. The Court has restricted and later approved of the use of drugs during the free exercise of religion. Lastly, the Court has continually reinforced the supremacy of the federal government over the states, in turn limiting the ability of the states to consider marijuana legislative reform.